2017
DOI: 10.3389/fpsyt.2017.00073
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Complex Post-traumatic Stress Disorder and Post-traumatic Stress Disorder in a Culturally Distinct, Conflict-Affected Population: A Study among West Papuan Refugees Displaced to Papua New Guinea

Abstract: Background: Controversy continues about the validity of the construct of complex post-traumatic stress disorder (C-PTSD). In particular, questions remain whether C-PTSD can be differentiated from post-traumatic stress disorder (PTSD) and, secondarily, other common mental disorders. The examination of these issues needs to be expanded to populations of diverse cultural backgrounds exposed to prolonged persecution. We undertake such an inquiry among a community sample of West Papuan refugees exposed to extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 48 publications
1
30
2
Order By: Relevance
“…This finding is considerably higher than reported by Silove et al (2017) and Ben-Ezra et al (2018), with CPTSD prevalence estimates of 3% and 2.6%, respectively, but lower than a multicultural refugee sample of whom 32.8% met the CPTSD criteria (Nickerson et al, 2016). However, given the context of the traumatic exposure that these individuals faced during their childhood, this finding is not surprising.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This finding is considerably higher than reported by Silove et al (2017) and Ben-Ezra et al (2018), with CPTSD prevalence estimates of 3% and 2.6%, respectively, but lower than a multicultural refugee sample of whom 32.8% met the CPTSD criteria (Nickerson et al, 2016). However, given the context of the traumatic exposure that these individuals faced during their childhood, this finding is not surprising.…”
Section: Discussioncontrasting
confidence: 57%
“…The model that included two second-order latent variables, PTSD and DSO (Model 7), to explain the covariation among the seven first-order factors also fitted the data; however, the chi-squared difference test indicated that Model 3 provided a significantly better fit to the data. Previous studies have found mixed support for the alternative factor models, with some evidence indicating model superiority for a second-order two-factor model with six correlated first-order factors (Hyland et al, 2017; Karatzias et al, 2016; Nickerson et al, 2016) and others finding support for a higher-order one-factor model representing CPTSD and six second-order factors (Silove et al, 2017). However, an important difference between these studies and the current study is that the AD factor was estimated as a unidimensional construct and the study conducted by Silove and colleagues did not estimate a correlated first-order model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study was undertaken in order to provide (i) the first assessment of the factorial validity of the ITQ amongst an Arabic‐speaking sample of refugees from the Middle East and (ii) the first assessment of the clinical utility of the ITQ within a low‐resourced, humanitarian setting. Building on previous studies which estimated the prevalence rates of PTSD and CPTSD amongst refugees and internally displaced persons , the current study represents the first assessment of the prevalence rates of ICD‐11 PTSD and CPTSD using a disorder‐specific measure ITQ. Prevalence rates of PTSD (25.2%) and CPTSD (36.1%) in this group of treatment‐seeking Syrian refugees were similar to those observed within another treatment‐seeking refugee sample resettled in Switzerland (PTSD = 19.7%, CPTSD = 32.8%) .…”
Section: Discussionmentioning
confidence: 99%
“…To date, only four studies have investigated the nature of ICD‐11 PTSD/CPTSD amongst refugee and internally displaced samples. The factorial validity of ICD‐11 PTSD and CPTSD has been supported in two studies with West Papuan refugees resettled in Papa New Guinea ( N = 230, and N = 250). Nickerson et al also found evidence to support the factor structure of CPTSD amongst a nationally diverse, treatment‐seeking sample of refugees ( N = 134) resettled in Switzerland.…”
Section: Introductionmentioning
confidence: 91%